Detection of Psychotropic Compound in Coprophilous Fungi in District of Baturraden Banyumas Regency - Amanda, Safira; Mumpuni, Aris; Ekowati, Nuraeni (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2021)
Coprophilous fungi or dung-loving fungi are fungal group which adapted to life on dung and fecal of herbivorous animals. Coprophilous fungi contain psychotropic compounds, substances or drugs, both natural and synthetic, but not narcotics. This compound comprises psychoactive properties that cause selective influence on the central nervous system and lead distinctive changes in mental activity and behavior. Chemical Spot Test still remain an important method for the preliminary identification of illicit drugs and other psychotropic compound in spite of developments in instrumental technology which enables to use in field. Banyumas Regency, especially Baturraden district is a very potential habitat for coprophilous fungi due to a lot of cattle farms were established there. In addition, the environmental condition also suitable for the fungal growth. This study aim to make an inventory and identify the coprophilous fungi that found in District of Baturraden Banyumas Regency and detect the presence of psychotropic compound in that fungi. The research will be conducted using purposive random sampling and Color Test or Chemical Spot Test analysis. The obtained data is analyzed descriptively by comparing with Atlas of The Munsell Color System. This research obtained seven genera of coprophilous fungi i.e: Coprinellus sp., Coprinopsis sp., Entoloma sp., Gymnopus sp., Lepiota sp., Parasola sp. and Stropharia sp. that discovered in two cattle farms in Baturraden District. Key Words: coprophilous, fungi, psychotropic